Linkages between geochemistry and microbiology in a proglacial terrain in the High Arctic. Issue 77 (4th March 2019) - Wojcik, Robin; Donhauser, Johanna; Frey, Beat; Holm, Stine; Holland, Alexandra; Anesio, Alexandre M.; Pearce, David A.; Malard, Lucie; Wagner, Dirk; Benning, Liane G.
ABSTRACT: Proglacial environments are ideal for studying the development of soils through the changes of rocks exposed by glacier retreat to weathering and microbial processes. Carbon (C) and nitrogen (N) contents as well as soil pH and soil elemental compositions are thought to be dominant factors structuring the bacterial, archaeal and fungal communities in the early stages of soil ecosystem formation. However, the functional linkages between C and N contents, soil composition and microbial community structures remain poorly understood. Here, we describe a multivariate analysis of geochemical properties and associated microbial community structures between a moraine and a glaciofluvial outwash in the proglacial area of a High Arctic glacier (Longyearbreen, Svalbard). Our results reveal distinct differences in developmental stages and heterogeneity between the moraine and the glaciofluvial outwash. We observed significant relationships between C and N contents, δ 13 Corg and δ 15 N isotopic ratios, weathering and microbial abundance and community structures. We suggest that the observed differences in microbial and geochemical parameters between the moraine and the glaciofluvial outwash are primarily a result of geomorphological variations of the proglacial terrain.